Javnozdravstveni vidiki preprečevanja napak nevralne cevi s folno kislino - Farkaš-Lainščak, Jerneja (Zdravstveno varstvo, 2009)
Neural tube defects are a group of heterogenous and complex congenital anomalies of the central nervous system. Adequate intake of folic acid prior to conception and during early pregnancy prevents 60%-70% of primary and 72% of recurrent neural tube defects. To effectively reduce the prevalence of neural tube defects, numerous activities at all levels of prevention have to be conducted simultaneously. These include: promoting healthy diet, taking folic acid supplements, fortifying staple foods with folic acid, and introducing prenatal screening and treatment. Folic acid fortification of staple foods has proved potentially effective in preventing some chronic noncommunicable diseases. Nonetheless, some ethical dilemmas and professional problems remain unsolved.
Keywords: centralno živčevje; folna kislina; napake; preventiva; razvoj